Collaboration as Process: The Making of a Partnership to Serve At‐Risk Youths of Haitian Descent. Issue 1 (8th March 2021) - Marcelin, Louis Herns; Dembo, Richard; Cela, Toni; Burgos, Catherimarty; Copeland, Morris; Page, Bryan
Abstract: The increasingly intractable nature of many social problems has given rise to cross‐institutional and interdisciplinary collaborations in order to respond to social problems that no single entity can resolve on its own. One value of anthropology lies in its capacity to provide culturally tailored strategies for successful collaboration between different stakeholders in communities, across disciplinary fields, among public policymakers and practitioners. In this article, we revisit the emergence of a collaborative initiative to support at‐risk youths of Haitian descent and their families. This work was undertaken by university researchers, juvenile justice professionals in Miami‐Dade County, and community‐based practitioners. Guided by a holistic anthropological perspective and a multidimensional approach to collaboration, we provide a processual analysis of almost two decades of opportunities and challenges posed by our collaboration and illuminate the importance of collaboration in identifying evidence‐based solutions to social problems. While not all collaborative teams experience the same processes or operate within the same sociocultural contexts, we argue that there are some fundamental principles to establishing effective collaboration: a shared common goal, shared objectives, and time.